773 Standardising Autologous Breast Reconstruction Referrals – a Quality Improvement Project. (19th August 2022) - Hardwick, E; Rutherford, C; Johnson, L; Oezdogan, Y
Abstract: Aim: Autologous breast reconstruction should be discussed with all suitable patients undergoing mastectomy, reinforced by the most recent Oncoplastic guidelines. This generates a large volume of referrals to the Plastics team, which are variable in content, and may neglect pertinent information. The aim of this project was to prospectively audit the quality of plastics referrals prior to the introduction of a standardised proforma with the aim of streamlining the patient pathway. Method: A prospective audit of 19 consecutive referrals for autologous breast reconstruction was performed in December 2021 in a single centre. Referrals were assessed for the following essential data: immediate or delayed surgery, BMI, smoking status, neoadjuvant chemotherapy, and planned adjuvant treatment, specifically chemoradiotherapy. Results: Immediate or delayed reconstruction status was reported in 18 (94.7%) of referrals made. Neoadjuvant chemotherapy was mentioned in 13 (68.4%) referrals. Plans for likely adjuvant treatment, including radiotherapy was mentioned in 15 (78.9%) referrals. Co-morbidities were reported in 6 (31.6%) referrals. Only 2 (10.5%) referrals reported on BMI and 4 (21.1%) on smoking status. Conclusion: There is significant variability in the detail and quality of referrals for autologous breast reconstruction. Consequently, a standardised proforma was introduced to the unit which was presented at the Trust Audit Day. The proforma information was felt to be crucial in assessing the patient's appropriateness for surgery and its timing. This referral was introduced as an online tick-box form sent to a shared Plastics email. This has since been widely adopted allowing for efficient time-saving referrals with relevant information included.